2014
DOI: 10.1080/09583157.2014.942595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an entomopathogenic nematode,Steinernema carpocapsaeon haemocyte profile and phenoloxidase activity of the Colorado potato beetle,Leptinotarsa decemlineata

Abstract: The Colorado potato beetle (CPB), Leptinotarsa decemlineata Say is the most destructive insect pest of potato in many areas of the world. Little is known about the haemocyte types of the CPB and its plasma phenoloxidase (PO). In this regard, we investigated the haemocyte profile and PO of CPB and its immune response to the entomopathogenic nematode, Steinernema carpocapsae. Five types of haemocytes, the plasmatocytes (~67.4%), granulocytes (~23.5%), oenocytoids (~2.4%), spherulocytes (~0.25%) and prohaemocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In contrast, a significant decrease was found after treatment with 2 Gy irradiated H. bacteriophora or S. scapterisci. The increase in phenoloxidase activity was previously stated by Ebrahimi, Niknam, Dunphy, and Toorchi (2014) on Leptinotarsa decemlineata treated with S. carpocapsae. Concerning to the report of Gupta (2001, p. 6) who postulated that the humoral immune response of insect include synthesis of antimicrobial peptides such as lysozyme (which is protective enzymes against pathogens by damaging the bacteria cell walls (Peters, Kruse, Pollwein, Grzeschik, & Sippel, 1989) and activation of the prophenoloxidase to phenoloxidase for melanisation of nodules, we could state that the increase in phenoloxidase and lysozyme activities may regard to the immune response of larvae to the nematodes, while the decrease was due to the winning of the nematodes on larval immune system; as the 2 Gy irradiated H. bacteriophora or S. scapterisci kill the larvae faster than the normal one.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, a significant decrease was found after treatment with 2 Gy irradiated H. bacteriophora or S. scapterisci. The increase in phenoloxidase activity was previously stated by Ebrahimi, Niknam, Dunphy, and Toorchi (2014) on Leptinotarsa decemlineata treated with S. carpocapsae. Concerning to the report of Gupta (2001, p. 6) who postulated that the humoral immune response of insect include synthesis of antimicrobial peptides such as lysozyme (which is protective enzymes against pathogens by damaging the bacteria cell walls (Peters, Kruse, Pollwein, Grzeschik, & Sippel, 1989) and activation of the prophenoloxidase to phenoloxidase for melanisation of nodules, we could state that the increase in phenoloxidase and lysozyme activities may regard to the immune response of larvae to the nematodes, while the decrease was due to the winning of the nematodes on larval immune system; as the 2 Gy irradiated H. bacteriophora or S. scapterisci kill the larvae faster than the normal one.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding to the rate of reproduction of irradiated nematode, Ebrahimi, et al (2014) and Gupta (2001) indicated that, insect host killing may be affected by the decrease in the lysozyme and phenoloxidase activities which observed in the treated insect larvae that means the suppression in the immune system responses against any pathogen. This illustrated why they die faster, and the nematode can propagate more than do in the unirradiated larvae.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies investigated the infection of EPNs on PO activity of host insects (Brivio et al 2002;Walter et al 2008;Ebrahimi et al 2014aEbrahimi et al , 2014bKramarz et al 2016). PO is the key component of insect humeral immune system.…”
Section: Plasma Phenoloxidase Activitymentioning
confidence: 99%